1995
DOI: 10.1152/ajpgi.1995.269.1.g22
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of somatostatin on the canine ileal circular muscle

Abstract: The aim of this study was to investigate the mechanism of action of somatostatin on the circular muscle of the isolated canine ileum using the microelectrode technique. The membrane potential from circular muscle cells was recorded in two preparations: 1) whole thickness circular and longitudinal muscle (with intact myenteric and deep muscular plexuses, n = 13) and 2) isolated circular muscle (with only deep muscular plexus, n = 9). In this preparation, inhibitory junction potentials (IJPs), elicited after fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In conscious rabbit, somatostatin increases the pressure necessary to pass fluid through the ICS 75 . This potential increase in tone is in accordance with the depolarizing effect of somatostatin on ileal circular muscle through the inhibition of the release of NO‐related compound 76 …”
Section: Humoral Control Of the Icssupporting
confidence: 76%
“…In conscious rabbit, somatostatin increases the pressure necessary to pass fluid through the ICS 75 . This potential increase in tone is in accordance with the depolarizing effect of somatostatin on ileal circular muscle through the inhibition of the release of NO‐related compound 76 …”
Section: Humoral Control Of the Icssupporting
confidence: 76%
“…Apamin is a pharmacological tool widely used to discriminate between the fast and the slow component of the IJP and even nowadays the term "apamin sensitive" vs. "apamin insensitive" IJP is often used in the literature. Apamin reduces the IJPf in several areas of the gastrointestinal tract and in several species (22,38,39,43,46,49). However, the slow component is also partially reduced by apamin in the human colon (23) and smallconductance calcium-activated potassium channel (SK Ca ) channels might participate in nitrergic neurotransmission in the ileum of the hamster (28) and in the esophagus of the opossum where the junction potential is mainly nitrergic (5).…”
Section: Gil V Gallego D Moha Ou Maati H Peyronnet R Martínez-cutmentioning
confidence: 99%
“…The presence of Som in the digestive system had been well described (Costa et al, 1980;Ekblad et al, 1988), but contrasting results have been obtained regarding its actions on intestinal smooth muscle. In fact, it has been reported that through activation of inhibitory neurons and/or inhibition of excitatory neurons, Som caused muscle relaxation in guinea-pig intestine in vitro (Furness and Costa 1979), while it inhibited NO release and thereby excited intestine circular muscle in canine ileum in vivo (Jimenez et al, 1995). It has been shown that rat ICC-DMP express a particular subtype of Som receptors, sst 2A , and are surrounded by Som-IR nerve endings (Sternini et al, 1997).…”
Section: Icc and Somatostatin (Som) Receptorsmentioning
confidence: 99%